2023
DOI: 10.1088/1755-1315/1148/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Biodiversity of Benthic Infauna at Seagrass Ecosystem in Three Small Islands of Northern Papua, Indonesia: Liki Island, Meossu Island and Befondi Island

Abstract: One of the ecological roles of seagrass ecosystems is as a habitat for marine organisms. Benthos is a group of marine biota that lives on the bottom of the waters and can be found in seagrass ecosystems. This study aims to inventory the diversity of benthic organisms in seagrass ecosystems in Liki, Befondi and Meossu island. This research is part of the second leg of the Nusa Manggala Expedition which was held in 2018 on Liki Island, Meossu and Befondi, the northern waters of Papua.. Benthos data was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…The most dominant species was from genus Cerithium (e.g Cerithium balteatum, Cerithium punctatum, and Cerithium rostratum). This result was in line with several studies which focused on associated fauna in seagrass beds in Malaysia (Illias et al, 2021;Vian et al, 2022) and Indonesia (Tasabaramo et al, 2023).…”
Section: Comparisons Of Benthic Fauna Diversity Between Different Mea...supporting
confidence: 91%
See 2 more Smart Citations
“…The most dominant species was from genus Cerithium (e.g Cerithium balteatum, Cerithium punctatum, and Cerithium rostratum). This result was in line with several studies which focused on associated fauna in seagrass beds in Malaysia (Illias et al, 2021;Vian et al, 2022) and Indonesia (Tasabaramo et al, 2023).…”
Section: Comparisons Of Benthic Fauna Diversity Between Different Mea...supporting
confidence: 91%
“…The results of this study show there were 5 groups of taxa found among the meadows, which were Gastropods, Bivalvia, Echinoderms, Decapods, and Amphipods. These groups of taxa were the most common found in the seagrass beds and were congruent with other studies' findings conducted in Akkeshi Bay, Japan (Yamada et al, 2007), Virgin Islands, USA (Valdez et al, 2021) Gazumbo Island, Malaysia (Vian et al, 2022), Barra Grande Beach, Brazil (Cavalcante et al, 2019), Philippines (Wagey et al, 2017), Barrang Lompo Island, Indonesia (Ambo-rappe, 2016), and Northern of Papua, Indonesia (Tasabaramo and Nugraha, 2023).…”
Section: Seagrass Conditionssupporting
confidence: 90%
See 1 more Smart Citation